2006
DOI: 10.4028/www.scientific.net/kem.326-328.1331
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Cracked Specimen for Biaxial Tensile Loading Test

Abstract: In the recent years, the studies on the mechanical behaviors of various materials subjected to biaxial loading have been worked since they are more complicated and intrinsically different from those under the simple uniaxial condition. The cruciform specimen without any slots has been commonly used for the goal so far. We prepare improved biaxial specimen with slots and make sure its validity by means of finite element analysis and photoelastic experiment. Even though the equal load biaxiality was applied to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Shimamoto et al [11] obtained the stress intensity factors according to various biaxial load ratios in the cruciform specimens of elastic and anisotropic material by the photoelastic and caustic methods. Shin et al [12] suggested the improved cruciform biaxial specimen with slots in the loading parts and ascertained its validity by means of finite element analyses and photoelastic experiments. Shin's paper [12] showed that, even though the load biaxiality ratio γ =1, the stress biaxiality ratios in central region of cruciform biaxial specimen differ according to the position from the center of specimen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shimamoto et al [11] obtained the stress intensity factors according to various biaxial load ratios in the cruciform specimens of elastic and anisotropic material by the photoelastic and caustic methods. Shin et al [12] suggested the improved cruciform biaxial specimen with slots in the loading parts and ascertained its validity by means of finite element analyses and photoelastic experiments. Shin's paper [12] showed that, even though the load biaxiality ratio γ =1, the stress biaxiality ratios in central region of cruciform biaxial specimen differ according to the position from the center of specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Shin et al [12] suggested the improved cruciform biaxial specimen with slots in the loading parts and ascertained its validity by means of finite element analyses and photoelastic experiments. Shin's paper [12] showed that, even though the load biaxiality ratio γ =1, the stress biaxiality ratios in central region of cruciform biaxial specimen differ according to the position from the center of specimen. Therefore, we use the word, "equal biaxial tensile load" that is, not "equal biaxial tensile stress.…”
Section: Introductionmentioning
confidence: 99%